Improving Writing Ability Through Concept Sentence For The Eleventh Grade Students Of SMA N 1 Tunjungan BloraIn 2012/2013 Academic Year - Shantika, Elistya Reza Ayu, Drs. Djoko Srijono, M.Hum, Dr Anam Sutopo M. Hum (2013)
This research is aimed at describing the writing ability improvement through concept sentence in SMA N 1 Tunjungan Blora and describing whether teaching writing by using concept sentence can improve the writing ability or not. This is a descriptive qualitative research. The writer applies classroom action research (CAR) which requires four steps, namely: planning, acting, observing, and reflecting. The subject of the research is the eleventh grade of IPA.4 students of SMAN 1 Tunjungan Blora in 2012/2013 academic year. This class consists of eight male students and twenty two female students. This class is chosen because it has low ability in writing. The method of collecting data is conducted by doing: observation, interview, test, and document analysis. The methods of collecting data are as follows: observing, interviewing, test, and document analysis. In analyzing the quantitative data the writer applied descriptive comparative technique while in analyzing the qualitative data she applied critical analyzing technique. The result of this research shows that teaching writing through concept sentence can improve the students‟ writing ability. It is proved by the improvement of the students‟ mean score. The mean score of pre-test is 70,7 while the mean score of post-test is 86,7. In addition, the students also feel interested, enthusiastic, motivated and easy in writing class. They also feel easy to express their ideas because the teacher gives keywords as the concept sentence